A Brief Analysis of the Acrostic in Chinese Language in Teaching Chinese as a Foreign Language - Lydia Anggreani; Agustian Agustian (Bina Nusantara University, 2014)
Acrostic is a special phenomenon of the modern Chinese language. It is a combination of lexical and syntactical that across “vocabulary” and “grammar” categories. The morphemes can be combined and can also be separated by various form changes depending on its development. Acrostic is always been a crucial part in teaching Chinese language to foreigners and less developed than other parts of the teaching. This study used quantitative method to analyze the problems associated with the acrostic in teaching Chinese to foreigners. Source of the data was learners’ exercise and assignment. The discussion in this article was viewed from the perspective of the outside-oriented teaching, grouped into 3 main sections. The first was in terms of the usability characteristics to the acrostic developments in the acrostic grammar study. The second, based on the results of the questionnaire regarding the use of acrostic, research analyzed students’ main mistakes and their causes. The third was to observe the condition of teaching acrostic. This research is expected to help teachers and learners of Mandarin understand and overcome the difficulties in learning acrostic.